Social Media Utilization for Self-Regulated English Learning during COVID-19 Outbreaks - Maulina Maulina; Rahmat Nasrullah; Risman Wanci (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2022)
It is quite challenging at this moment for undergraduate students to study from home (SFH) during the COVID-19 outbreaks. Social distancing practices applied during the coronavirus outbreaks to most of the public settings, including at academic activities at university. Fortunately, there have been many platforms of social media provided and accessed easily in this digital era. This current study aimed at investigating and understanding higher education students’ perspectives on social media in learning English independently in the COVID-19 outbreak. Researchers used an online survey as the main research instrument to gather data from 147 potential students to be the respondents to fill out the survey from three universities in the Sulawesi region, Indonesia. The result showed that 81% of respondents used WhatsApp as the medium to study autonomously at home during the pandemic. Besides, YouTube (77.6%), Instagram (57.8%), Facebook (29.3%), and Twitter (24.5%) also became the additional choices. They used those friendly-users and cheap accessed social media platforms to watch and to listen to English videos (79.6%) also to have the written chats in English with friends and teachers (67.3%) as well as to have the audio and video calling in English (36.1%). Further, during the pandemic, respondents improve their speaking skills (37.4%), listening skills (29.3%), reading skills (17%), and writing skills (16.3%) through social media. Even though the world is distracted, university students in this region keep their motivation to learn English from home autonomously.